Mindfulness Meditation and Anxiety in Nursing Students. Issue 4 (July 2020) - Stinson, Cynthia; Curl, Eileen Deges; Hale, Gina; Knight, Stacey; Pipkins, Cynthia; Hall, Iva; White, Kelli; Thompson, Nancy; Wright, Christy
Abstract : Abstract: This quasi-experimental study used a convenience sample of nursing students ( n = 49) to evaluate the effectiveness of mindfulness meditation on anxiety. Students participated in mindfulness meditation sessions and completed the State-Trait Anxiety Inventory. A statistically significant reduction in trait anxiety was found in the intervention group ( p = .000); state anxiety decreased but not significantly. In contrast, anxiety increased significantly in the comparison group, but progression was not significantly different between groups. Trait anxiety may decrease with mindfulness meditation.